Chinese Community under the Soekarno Era in Indonesia - Permana, Septian Aji; Purwantiningsih, Ary (History Department, Semarang State University and Historian Society of Indonesia, 2021)
Abstract: This study aims to analyze the life of Chinese people in Indonesia during the Soekarno government and analyze the governmentÃ¢â‚¬â„¢s treatment of Chinese people in the Soekarno era. This study used a historical method approach with a limited history across the 1930s period, from 1941 to 1958, from 1959 to 1966. The method used is as follows: data collection in the form of literature studies relevant to the subject matter discussed, source criticism to find out the relevant elements through the incorporation of information obtained through the source, and compilation i.e., writing historical facts. Political and economic perceptions influenced Chinese ethnic communities in Indonesia during colonial, the old order, and the new times. Chinese society received many sanctions from the Soekarno government because of communist ideology, which was a threat to the government. The existence of ethnocentric during the old order so that Chinese people cannot be received well.Ã‚Â Abstrak: Penelitian ini bertujuan untuk menganalisis kehidupan masyarakat Tionghoa di Indonesia pada masa pemerintahan Soekarno dan menganalisis perlakuan pemerintah terhadap orang Tionghoa pada masa pemerintahan Soekarno. Penelitian ini menggunakan pendekatan metode sejarah dengan sejarah terbatas pada periode tahun 1930-an, dari tahun 1941 hingga 1958, dari tahun 1959 hingga tahun 1966. Metode yang digunakan adalah sebagai berikut: pengumpulan data berupa studi pustaka yang relevan dengan materi pelajaran yang dibahas, kritik sumber untuk mengetahui unsur-unsur yang relevan melalui penggabungan informasi yang diperoleh melalui sumber, dan kompilasi yaitu, menulis fakta sejarah. Persepsi politik dan ekonomi mempengaruhi komunitas etnis Tionghoa di Indonesia pada masa penjajahan, Soekarno, dan Orde Baru. Masyarakat Tionghoa banyak mendapat sanksi dari pemerintah Soekarno karena ideologi komunis yang menjadi ancaman bagi pemerintah. Adanya etnosentris pada masa Soekarno sehingga masyarakat Tionghoa tidak bisa diterima dengan baik.Ã‚Â